Broken Heart Syndrome in a Patient on Maintenance Hemodialysis. (June 2017) - Bhogal, Sukhdeep; Ladia, Vatsal; Sitwala, Puja; Bajaj, Kailash; Ramu, Vijay; Paul, Timir
Context: Broken heart syndrome or Takotsubo cardiomyopathy (TC) is a disorder characterized by transient left ventricular apical ballooning that almost invariably precedes emotional or physical stress. Although the patients with chronic kidney disease on hemodialysis have shown to exhibit sustained activity of sympathetic nervous system, the presentation of TC in these patients is a rare entity with few case reports in the literature.Case Report: A 75-year-old female with past medical history of end-stage renal disease presented with chest pressure and heaviness that started during her maintenance hemodialysis session. Electrocardiogram showed ST elevation and T wave inversion in V3-V6 leads. Emergent left heart catheterization was done that showed normal coronaries and akinesis of apical left ventricle wall consistent with TC. She was started on maximal medical management and underwent hemodialysis the next day without recurrence of the symptoms.Conclusion: TC may an underdiagnosed entity in patients on hemodialysis. However, it should be considered in the differential diagnosis in hemodialysis patients, particularly who presents with chest pain and/or symptoms.